Multifaceted functions of the Wilms tumor 1 protein: From its expression in various malignancies to targeted therapy - Qing Nian; Yan Lin; Jinhao Zeng; Yanna Zhang; Rongxing Liu (Translational Oncology)
Wilms tumor 1 (WT1) is a multifaceted protein with dual functions, acting both as a tumor suppressor and as a transcriptional activator of oncogenes. WT1 is highly expressed in various types of solid tumors and leukemia, and its elevated expression is associated with a poor prognosis for patients. High WT1 expression also indicates a greater risk of refractory disease or relapse. Consequently, targeting WT1 is an effective strategy for disease prevention and relapse mitigation. Substantial information is available on the pathogenesis of WT1 in various diseases, and several WT1-targeted therapies, including chemical drugs, natural products, and targeted vaccines, are available. We provide a comprehensive review of the mechanisms by which WT1 influences malignancies and summarize the resulting therapeutic approaches thoroughly. This article provides information on the roles of WT1 in the pathogenesis of different cancers and provides insights into drugs and immunotherapies targeting WT1. The goal of this work is to provide a systematic understanding of the current research landscape and of future directions for WT1-related studies.